THE DIDACTIC SIGNIFICANCE OF THE DEVELOPMENT OF PHYSICAL QUALITIES THROUGH NATIONAL OUTDOOR GAMES FOR STUDENTS IN GRADES 1-2 OF SECONDARY SCHOOLS (Scientific journal of the Fergana State University, 2024)
This article examines the features of the formation of physical qualities of the methods of national sports games and analyzes how national sports games are the most effective way to improve the physical qualities of children. The instruction not to carelessly use natural movements in the gameplay is disclosed in a recommendation form.